(untitled) (Revista Científica Compendium, 2024)
As a result of a documentary review with a qualitative approach, this research proposes an analytical-interpretative of the constructs: approach of capabilities, personal growth and effective social inclusion, and their relationship with Sustainable Development Goal No. 5; as possibilities, which, once put into synergistic relationship, are estimated as a hopeful alternative to transcend towards a scheme of integral human development for women. The results indicate that the combination of substantial freedoms and related personal capabilities entails necessary mechanisms to consolidate the ideals of inclusive social justice. In conclusion, the search for a new social order that allows for effective performance and the consolidation of a dignified life requires expanding freedoms and capabilities that favor social positioning and access to possibilities for permanent growth.